Group Counseling Cognitive Restructuring Techniques to Reduce Fear of Missing Out (FoMO) Behavior - Widadiyah, Zulfa Nazwa; Wibowo, Bangun Yoga; Wahyuningsih, Lenny (IAIN Kudus, 2024)
Group Counseling With Cognitive Restructuring Techniques To Reduce Fear Of Missing Out Behavior. The implementation of this research aims to test the effectiveness of group counseling services in reducing Fear of Missing Out (FoMO) behavior among adolescents. The increasing prevalence of FoMO among teenagers impacts self-statements and thoughts, leading to irrational and negative tendencies. The used method was a quasi-experimental method with a nonequivalent control group design. The research sample consisted of 12 eleventh-grade students of SMAN 6 Tangerang, divided into two groups: an experimental group receiving treatment using group counseling with cognitive restructuring techniques and a control group receiving group counseling without cognitive restructuring techniques. Data collection utilized a FoMO scale questionnaire. The results indicated a significant decrease in FoMO behavior in the experimental group compared to the control group. Through this research, it was found that group counseling service with cognitive restructuring technique is effective in reducing Fear of Missing Out (FoMO) behavior, as evidenced by the Asymp. Sig. value (2-tailed) is 0.004, which is less than 0.05.Keywords: Group Counseling; Cognitive Restructuring; Fear of Missing Out; Adolescence